FORMULASI PENGATURAN PENYELESAIAN EXTRA JUDICIAL KILLING DALAM PENGADILAN HAK ASASI MANUSIA DI INDONESIA - Patricia Regita Aryani (2022)
Extra Judicial Killing as an act that has a criminal element with no respect for human rights. As in the case of the death of six HRS bodyguards where the incident Komnas HAM said not as a gross human rights violation while Amnesty International Indonesia said as Extra Judicial Killing but both stated the case should be tried in a criminal court not a human rights court. There is a vagueness of the arrangement of Extra Judicial Killing as a gross human rights violation contained in Law No. 39 of 1999 with Law No. 26 of 2000. This research is normative legal research with a statutory, conceptual, and comparative approach. The data collected is primary and secondary data with qualitative analysis methods. Extra Judicial Killing arrangements in the international world are only known as murders that if they occur must be punished. Indonesia and the United States are among the countries that have express Extra Judicial Killing arrangements, while many countries only regulate it implicitly such as Nigeria and Bangladesh. This research seeks to provide an ideal concept of Extra Judicial Killing arrangements in Indonesia by comparing the legal arrangement of Extra Judicial Killing between Indonesia and the United States. Based on legal comparisons that have been done, it is found that the extra judicial killing arrangement in Indonesia is still incomplete compared to the arrangements in the Torture Victim Protection Act 1991. But the U.S. Extra Judicial Killing arrangement is not yet complete enough so it needs to be added to the concept as a regulatory formulation with reference to the International Convention for Protection of All Persons from Enforced Disappearance 2006.